The polyphase evolution of the mafic rocks of the Juiz de Fora Complex: The record of two supercontinent cycles - Nunes Manoel, Talitta (2023)
The Juiz de Fora Complex (JFC) in the Araçuaí-Ribeira orogenic system, southeastern Brazil, is a basement unit displaying a variety of rock types that is tectonically imbricated with the supracrustal rocks of the Raposos Group in the Upper Thrust System of the Occidental Terrane, Ribeira Belt. Here we report new petrological, geochemical, and zircon U–Pb and Lu–Hf isotopic data on mafic garnet-granulites from the JFC with a view to evaluate the timing and P-T conditions of the collisional event as well as protolith formation. This work presents the most comprehensive metamorphic study on the Juiz de Fora Complex rocks to date. Metamorphic P-T estimates for the metamorphic peak conditions of 800–900 °C and 8–9 kbar in basic garnet-bearing granulites were obtained for the JFC, indicating that metamorphism took place at deeper crustal levels. Geochemical, zircon U–Pb geochronology, whole-rock Sm–Nd, Rb–Sr isotopes, and Lu–Hf isotopic data of mafic granulites yielded U–Pb ages of ca. 2201 Ma, and moderately juvenile εNd(t) = −0.5 and were obtained from the JFC marking the timing of volcanic arc magmatism during the Rhyacian period. This arc-related stage was followed by the post-collisional period during the Early Paleoproterozoic with ca. 1.94 Ga E-MORB signature granulites that shows evidence of magma sourced from Neoarchean (∼2.8 Ga) crust with addition of juvenile components. The high-grade metamorphism is possibly related to the final collision of the Congo and São Francisco Cratons at 590–560 Ma, which placed the Neoproterozoic metasediments and the JFC rocks at the same level. The integrated information sheds light on two collisional episodes where the oldest is represented by arc-related granulites during the Rhyacian Orogeny and the youngest is the higher-pressure Neoproterozoic overprint during the Brasiliano Orogeny.